2008
DOI: 10.1007/s10919-008-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Attaining Status at the Expense of Likeability: Pilfering Power Through Conversational Interruption

Abstract: Do status expectations affect how we interpret interruption in conversation?Two experiments examined how interrupters and their targets are perceived in same-and mixed-gender dyads. In Experiment 1, participants listened to a brief audiotaped conversation in which one person interrupted the other five times. In Experiment 2, four confederates (two men and two women) systematically interrupted naïve participants while discussing an article. In general, interrupters gained in status and targets of interruption l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…Finally, a coach who interrupts the client to ask a question (without showing any cues of friendliness) would show a dominant-neutral interpersonal behavior (cf. Aries et al 1983;Farley 2008; see Table 1). …”
Section: The Role Of Interpersonal Behavior In Coaching Interaction Pmentioning
confidence: 99%
“…Finally, a coach who interrupts the client to ask a question (without showing any cues of friendliness) would show a dominant-neutral interpersonal behavior (cf. Aries et al 1983;Farley 2008; see Table 1). …”
Section: The Role Of Interpersonal Behavior In Coaching Interaction Pmentioning
confidence: 99%
“…Other nonverbal parameters of speech such as volubility (time spent talking; Mast, 2002; Brescoll, 2012), successful interruptions (Farley, 2008), vocal expressivity (e.g., Dunbar and Abra, 2010), initiation of speech acts, and laughter (Gifford and Hine, 1994) have been linked with high interpersonal power. Likewise, volubility was the best predictor of observer-rated social performance in an interaction task (Stevens et al, 2010).…”
Section: Production Of Nonverbal Social Cues (Nvscs)mentioning
confidence: 99%
“…This confrontational language seems likely to backfire for women who have been found to suffer disproportionately negative consequences for expressing anger (Brescoll & Uhlmann 2008) or engaging in other aggressive behaviors associated with masculine communication styles (Farley, 2008;Bowles, Babcock & Lei, 2007). Students need more effective methods for responding to conflict such as those described in Wolfe and Powell's (2014) study of professional women engineers…”
Section: Resultsmentioning
confidence: 99%
“…No one's honest…We used to be kind of good friends.…and now I'm just, ugh, I can't deal with him (White female, public high research university, average) Such outbursts often had negative consequences: students reported losing friendships and falling in status after an angry confrontation. Moreover, anger is a dangerous strategy for women, who are perceived more negatively than men when displaying anger and other more aggressive communication strategies (Brescoll & Uhlmann, 2008;Farley, 2008;LaFrance, 1992). One female student discovered this double-standard the hard way when she mimicked one of her teammate's aggressive interruptions: There's actually this guy in our class, he loves to talk and he just won't let anyone get a word in.…”
Section: Avoidance Was a Common Solution But Often Carried High Costsmentioning
confidence: 99%